Thin circular composite panels subject to a central concentrated load - Yeoh, Yong Chen (2017)
This project provides an extensive study of the response of circular composite plates subjected to a central concentrated load. Finite element modeling (FEM) was employed to simulate the response of GLARE which has a layer of glass reinforced epoxy sandwiched between two thin aluminum layers, under different support & loading conditions. The convergence study was carried out to determine the economical mesh density for FEM analysis. The simulation was conducted under static structural analysis with two different approach, applied force and applied displacement on the moving indenter. It was found that applied displacement gave a much more stable response and this method was employed throughout the simulation. The structural response of GLARE plate with different support conditions such as clamped and simply supported conditions were studied accordingly. The results suggested that the presence of membrane strain energy in clamped GLARE plate dominates during large deformation of the plate. It was thus found that a much higher load was needed to achieve same level of deformation on clamped GLARE plate than on simply supported GLARE plate. At the same time, the effects of indenter diameter on the structural response of circular plates were analyzed and discussed. A linear relationship was found between the indenter diameter and the reaction force. An alternative simulation approach, an asymmetrical simulation was modeled and analysis were performed. Their results were compared with those obtained from the full model simulation. A good correlation between the results suggested the asymmetric model is more efficient in computing time and also giving a more converged results.